The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1152/jappl.1997.83.6.2048
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanism of the pressor response to obstructive and nonobstructive apnea

Abstract: Obstructive and nonobstructive apneas elicit substantial increases in muscle sympathetic nerve activity and arterial pressure. The time course of change in these variables suggests a causal relationship; however, mechanical influences, such as release of negative intrathoracic pressure and reinflation of the lungs, are potential contributors to the arterial pressure rise. To test the hypothesis that apnea-induced pressor responses are neurally mediated, we measured arterial pressure (photoelectric plethysmogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 19 publications
2
63
0
3
Order By: Relevance
“…Treatment with a bronchodilator for mild to moderate COPD improves respiratory function and exercise tolerance, but does not improve gas exchange abnormalities in the absence of oxygen therapy. 14 Nonetheless, in the present case tiotropium inhalation improved the airway obstruction and also suppressed activation of the sympathetic nerve system via an improvement in both the negative intrathoracic pressure 15,16 and the continuous fatigue of the respiratory muscles. Indeed, the plasma norepinephrine level was decreased significantly.…”
Section: Circulation Journal Vol70 December 2006mentioning
confidence: 54%
“…Treatment with a bronchodilator for mild to moderate COPD improves respiratory function and exercise tolerance, but does not improve gas exchange abnormalities in the absence of oxygen therapy. 14 Nonetheless, in the present case tiotropium inhalation improved the airway obstruction and also suppressed activation of the sympathetic nerve system via an improvement in both the negative intrathoracic pressure 15,16 and the continuous fatigue of the respiratory muscles. Indeed, the plasma norepinephrine level was decreased significantly.…”
Section: Circulation Journal Vol70 December 2006mentioning
confidence: 54%
“…RR duration is influenced by the baroreflex loop, reflects phasic sympathetic activity and interacts with power oscillations during apnoea or hyperventilation [5]. The increase in LFn power demonstrates central tonic sympathetic activation [5,19]. This is associated with an increase in respiratory effort due to the inspiratory attempts against the occluded/narrowed airways and the gradual elevation of negative intrathoracic pressure towards the end of apnoeas/hypopnoeas.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Their underlying pathological mechanisms include recurrent intermittent hypoxemia and increased sympathetic activity, primarily at the termination of the apneic events. 8,9 In a previous study, 10 our group showed that OSAS is also associated with ED in a dose-related fashion. This association is very strong in patients with severe OSAS and weaker in patients with mild or moderate OSAS.…”
Section: Introductionmentioning
confidence: 89%